2014
DOI: 10.1590/1415-52732014000600005
|View full text |Cite
|
Sign up to set email alerts
|

Away-from-home meals: Prevalence and characteristics in a metropolis

Abstract: A B S T R A C T ObjectiveThis study aimed to characterize away-from-home meals. MethodsThis population-based, cross-sectional study measured dietary intake by administering 24-hour recalls by telephone. Away-from-home breakfast, lunch, and dinner were described and characterized according to the foods that contribute most to the intake of energy, fat, sodium, and added sugar per meal. ResultsOf the 834 respondents, 24% had had at least one meal away from home. The average energy intake per away-from-home meal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(33 citation statements)
references
References 34 publications
(35 reference statements)
1
32
0
Order By: Relevance
“…From this perspective, we also found that not cooking one's meals was associated with overweight, which corresponds with the findings of Gorgulho et al [18] regarding the fact that adults who eat away from home present worse eating patterns. Their study showed that 24% of residents from the São Paulo (SP) metropolitan area ate at least one meal away from home/day, while in our sample, the prevalence was 15%.…”
Section: Itemssupporting
confidence: 91%
See 1 more Smart Citation
“…From this perspective, we also found that not cooking one's meals was associated with overweight, which corresponds with the findings of Gorgulho et al [18] regarding the fact that adults who eat away from home present worse eating patterns. Their study showed that 24% of residents from the São Paulo (SP) metropolitan area ate at least one meal away from home/day, while in our sample, the prevalence was 15%.…”
Section: Itemssupporting
confidence: 91%
“…Therefore, despite consuming a slightly higher amount of vegetables (+0.101g/100kcal; p<0.05), people who ate away from home tended to present a less healthy eating pattern, which corroborates our hypothesis regarding the relationship between UPF and SSB intake and overweight. Therefore, on this topic, we can state that although eating away from home is not synonymous with unhealthy meals or eating at fast-food restaurants, these environments may lead to consumption of unhealthy meals, especially among those who are not interested in improving their eating patterns [18,20,21]. Another fact that cannot be ignored is that in our study, 61.6% of the vegetarians reported having issues eating away from home.…”
Section: Itemsmentioning
confidence: 60%
“…Internationally, due to socioeconomic reasons, there are wide variations in this figure, with a study from Singapore reporting that 77.3% of their citizens eating outside [ 33 ]. In comparison, a study in Brazil reported only 24% of people to have at least one away from home meal [ 34 ]. In this study, we found no association between away from home meals and dietary sodium intake, which was an exciting finding in our study.…”
Section: Discussionmentioning
confidence: 99%
“…For the year of 2019, the forecast increased by 5% ( ANR - Associação Nacional de Restaurantes, 2018 ). Most of the meals taken outside the home are at lunch ( Gorgulho, Fisberg, & Marchioni, 2014 ), mainly on weekdays. As a result, companies' measures to adopt teleworking, the closure of a large part of local businesses, and the prohibition of serving the public harmed the sector.…”
Section: Introductionmentioning
confidence: 99%